154k views
19 votes
Okay Heather,santegelo

here you go ! I don’t know if your still on the main page but here it is!!!!

Okay Heather,santegelo here you go ! I don’t know if your still on the main page but-example-1
User TomG
by
5.3k points

1 Answer

7 votes


~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} \\\\[-0.35em] ~\dotfill


\cfrac{-3xyz}{-27x^2y^2z^2}\implies \cfrac{-3x^1y^1z^1}{-27x^2y^2z^2}\implies \cfrac{-3}{-27}\cdot \cfrac{1}{x^2x^(-1)y^2y^(-1)z^2z^(-1)} \\\\\\ \cfrac{1}{9}\cdot \cfrac{1}{x^(2-1)y^(2-1)z^(2-1)}\implies \cfrac{1}{9}\cdot \cfrac{1}{x^1y^1z^1}\implies \cfrac{1}{9xyz}

User Geemus
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.